Perjalanan Haji Indonesia di Masa Kolonial - Dawam Multazamy Rohmatulloh (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2017)
Hajj or pilgrimage is one of the important worship activities for Indonesian Muslims since past. Based on colonial archives, this paper describes thedynamics of the pilgrimage of Indonesia in the colonial period. The long duration of the trip, a tough challenge, and the high cost of travel is a “fee” to be paid by the pilgrims in the past. Moreover, the existence of many service provider of the pilgrimage also influence that dynamics. On the other hand, the colonial government also plays an important role by issuing a variety of regulations to ensure the “order” of the pilgrimage. Keywords: Hajj trip, company, regulation, colonial period.